Sempre en Galiza, Prohibited by the Franco Dictatorship - Dasilva, Xosé Manuel (Madrygal. Revista de Estudios Gallegos, 2023)
The main aim of this article is to analyse the numerous vicissitudes that Sempre en Galiza suffered throughout the Francoist period. First of all, it offers some information about the prohibition that prevented its publication in our territory for several decades. Next, attention is paid to those pages of Castelao’s essay that were included in the volumes Escolma posible (1963), published by Galaxia, and El pensamiento político de Castelao (1965), printed by Ruedo Ibérico in France. In the last part of the study, the censorship files of the initiatives related to Sempre en Galiza that were carried out, on the one hand, by the Vigo bookshop Librouro in 1975 and, on the other hand, by Akal Editor in 1976 and 1977, when the book was finally published in its entirety among us, are particularly examined.